2010
DOI: 10.1177/1933719110377237
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus GR-1-Induced IL-10 Production in Human Placental Trophoblast Cells Involves Activation of JAK/STAT and MAPK Pathways

Abstract: Intrauterine infection/inflammation complicates 25% to 40% of preterm births (PTB). The human vagina is normally populated by Lactobacillus species, some of which upregulate interleukin 10 (IL-10) output in lipopolysaccharide (LPS)-treated human placental trophoblast cells. We hypothesize that a probiotic strain, L rhamnosus GR-1 exerts its anti-inflammatory effect through activation of the Janus Kinases/Signal Transducers and Activators of Transcription (JAK/STAT) and mitogen-activated protein kinase (MAPK) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 39 publications
5
24
0
Order By: Relevance
“…STAT3 phosphorylation has been shown to be essential for the survival and proliferation of human trophoblast cells from JEG-3 lineage [42]. It has been shown that supernatants of Lactobacillus rhamnosus cultures induced STAT3 phosphorylation and IL10 production in human trophoblast cells, contributing to the immunosuppression at the maternal-fetal interface [43]. Mesenchymal stem cells from rat bone marrow down-modulated the maturation of murine dendritic cells when IL10 triggered the JAK1/STAT3 signaling pathway [44].…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 phosphorylation has been shown to be essential for the survival and proliferation of human trophoblast cells from JEG-3 lineage [42]. It has been shown that supernatants of Lactobacillus rhamnosus cultures induced STAT3 phosphorylation and IL10 production in human trophoblast cells, contributing to the immunosuppression at the maternal-fetal interface [43]. Mesenchymal stem cells from rat bone marrow down-modulated the maturation of murine dendritic cells when IL10 triggered the JAK1/STAT3 signaling pathway [44].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal STAT/suppressor of cytokine signaling (SOCS) signaling has been demonstrated in CD patients [110], and probiotics are also shown to modulate the JAK-STAT signaling in human placental trophoblast cells [111]. Increasing evidence further demonstrates that metabolism, xenobiotics, and nuclear receptor signaling are involved in the action of probiotics [67, 68].…”
Section: Mechanisms For Probiotics In Anti-inflammationmentioning
confidence: 99%
“…The probiotic mechanisms are believed to include the release of antibacterial substances, biosurfactant production, disruption of biofilms and competitive exclusion [16]. Furthermore, the ability of probiotic strains to modulate immunity through NF-κB and mitogen activated protein (MAP) kinase pathways, both important in the development of innate and adaptive immunity, has been reported [17,18]. Lactobacillus rhamnosus GR-1 is a probiotic isolated from a female urethra [19] used to prevent UTI and bacterial vaginosis, and it has both immunomodulatory and antimicrobial activity [20,21].…”
Section: Introductionmentioning
confidence: 99%